A novel non-parametric method for uncertainty evaluation of correlation-based molecular signatures : its application on PAM50 algorithm - Fresno, Cristóbal; González, Germán Alexis; Merino, Gabriela Alejandra; Flesia, Ana Georgina; Podhajcer, Osvaldo Luis; Llera, Andrea Sabina; Fernández, Elmer Andrés (2024)
Fil: Fresno, Cristóbal. Universidad Católica de Córdoba; Argentina.